2016
DOI: 10.17126/joralres.2016.003
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of dental trauma in a group of Chilean primary school teachers.

Abstract: Aim: To determine the knowledge and management of dentoalveolar trauma in primary school teachers in rural and urban schools in the district of Paillaco, Chile, in 2014. Methods: An observational study was conducted in 167 teachers in the city of Paillaco. A survey developed from the questionnaires proposed by McIntyre et al. and Yassen et al. was used. The survey, previously approved by 2 experts, was applied in person in the school facilities, after the application of a pilot test. Demographic characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…The knowledge scores of the participants at bassline revealed some deficiencies in the teachers’ knowledge of TDIs. This finding is similar to that of some other studies reporting knowledge deficiency about dental trauma among teachers [11, 18, 3134].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The knowledge scores of the participants at bassline revealed some deficiencies in the teachers’ knowledge of TDIs. This finding is similar to that of some other studies reporting knowledge deficiency about dental trauma among teachers [11, 18, 3134].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, four designed cases were used for assessment of the teachers’ practice regarding management of TDIs, which was deficient at baseline. This finding has also been noted in the similar studies conducted by Mohandas et al in India [5], Letelier et al in Chile [31] and Traebert et al in Brazil [11]. Since practice efficacy is influenced by the level of knowledge, any deficiency in the teachers’ practice can be related to their insufficient level of knowledge.…”
Section: Discussionsupporting
confidence: 78%
“…Participant knowledge at baseline indicated initial deficiencies in schoolteachers' understanding of TDI. This result is comparable to the findings of other studies that identified a lack of teacher knowledge regarding dental trauma management 25,26 …”
Section: Discussionsupporting
confidence: 88%
“…This result is comparable to the findings of other studies that identified a lack of teacher knowledge regarding dental trauma management. 25,26 Although many teachers were aware that dental trauma is an emergency situation and that a knocked-out permanent tooth should be preserved, they did not have proper knowledge of how to manage fractured and avulsed teeth. Initially, more than onethird of the surveyed teachers indicated that they would consider not searching for a tooth that has been knocked out of the mouth, as it will undoubtedly be lost.…”
Section: A Bivariate Linear Regression Analysis Presented Inmentioning
confidence: 99%
“…The questionnaire adopted in this study was developed based on a validated questionnaire deployed in the existing literature, 12–14 and its content was validated by a panel of senior researchers. Modifications were made to the survey instrument before its use in the main survey.…”
Section: Methodsmentioning
confidence: 99%